2010
DOI: 10.1038/ja.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

The spinosyn family of insecticides: realizing the potential of natural products research

Abstract: The spinosyns are a large family of unprecedented compounds produced from fermentation of two species of Saccharopolyspora. Their core structure is a polyketide-derived tetracyclic macrolide appended with two saccharides. They show potent insecticidal activities against many commercially significant species that cause extensive damage to crops and other plants. They also show activity against important external parasites of livestock, companion animals and humans. Spinosad is a defined combination of the two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(188 citation statements)
references
References 107 publications
2
171
0
15
Order By: Relevance
“…Spinosad was previously thought to be a reduced-risk biopesticide by United States Environmental Protection Agency due to its selective toxicity to non-target species and the lower potential for environmental damage, which is widely used in agriculture and stockbreeding (Kirst, 2010). Until now, spinosad has been shown to be non-target toxicity, the molecular mechanism has been paying more and more attention (Biondi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Spinosad was previously thought to be a reduced-risk biopesticide by United States Environmental Protection Agency due to its selective toxicity to non-target species and the lower potential for environmental damage, which is widely used in agriculture and stockbreeding (Kirst, 2010). Until now, spinosad has been shown to be non-target toxicity, the molecular mechanism has been paying more and more attention (Biondi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is relatively simple to generate many similar chemical structures, using either chemical or biochemical pathways. Thus, the MoA of these compounds can be studied using an approximation of the structure-activity relationship (SAR) (Tewary et al 2006;Bhardwaj et al 2010;Kirst 2010;Li et al 2013). This term describes a rapidly growing field of research that studies relationships between molecular structure (e.g., available hydroxyl (He et al 1997) or polymerization degree (Frackenpohl et al 2009)) and the physicochemical and biological response.…”
Section: Chemical Synthesis Of Natural Active Substancesmentioning
confidence: 99%
“…Tewary et al (2006) carried out a similar work with Aphis craccivora, and they observed that the position of double bonds in the C6-C3 system is important because it influences mitochondrial respiration; increasing the activity of phenylpropanoids by nonpolar substitutes such as methoxy groups enhances its penetration through the body cuticle and diffusion. In the spinosyn family, over 1000 analogs have been obtained and tested (Salgado and Sparks 2005), and their SARs have been evaluated (Kirst 2010). 1.…”
Section: Chemical Synthesis Of Natural Active Substancesmentioning
confidence: 99%
“…Several studies have shown that spinosyn has no long time persistence ability in plants, soil and other environments due to facile degradation by microbes present, whereby they partition them into organic matter and sediment with subsequent biotic degradation in the absence of light. Overall, they are easily subjected to diverse degradative pathways and metabolic mechanisms, and hence reduce their persistence in plants, and other environments (Kirst, 2010).…”
Section: Actinomycetes and Its Metabolitesmentioning
confidence: 99%